ZmRop1 participates in maize defense response to the damage of Spodoptera frugiperda larvae through mediating ROS and soluble phenol production. (15th December 2022) - Zhang, Haoran; Hu, Zongwei; Luo, Xincheng; Wang, Yuxue; Wang, Yi; Liu, Ting; Zhang, Yi; Chu, Longyan; Wang, Xiangping; Zhen, Yangya; Zhang, Jianmin; Yu, Yonghao
Abstract: As plant‐specific molecular switches, Rho‐like GTPases (Rops) are vital for plant survival in response to biotic and abiotic stresses. However, their roles in plant defense response to phytophagous insect's damage are largely unknown. In this study, the expression levels of nine maize RAC family genes were analyzed after fall armyworm (FAW) larvae infestation. Among the analyzed genes, ZmRop1 was specifically and highly expressed, and its role in maize response to FAW larvae damage was studied. The results showed that upon FAW larvae infestation, salicylic acid and methyl jasmonate treatment ZmRop1 gene transcripts were all down‐regulated. However, upon mechanical injury, the expression level of ZmRop1 was up‐regulated. Overexpression of ZmRop1 gene in maize plants could improve maize plant resistance to FAW larvae damage. Conversely, silencing of ZmRop1 increased maize plant susceptibility to FAW larvae damage. The analysis of the potential anti‐herbivore metabolites, showed that ZmRop1 promoted the enzyme activities of catalase, peroxidase and the expression levels of ZmCAT, ZmPOD, ZmRBOHA and ZmRBOHB, thereby enhancing the reactive oxygen species (ROS) production, including the content of O 2− and H2 O2 . In addition, overexpression or silencing of ZmRop1 could have influence on the content of the total soluble phenol through mediating the activity of polyphenol oxidase. In summary, the results illuminated our understanding of how ZmRop1 participate in maize defense response to FAW larvae damage as a positive regulator through mediating ROS production and can be used as a reference for the green prevention and control of FAW larvae.